Upregulation of KLK8 Predicts Poor Prognosis in Pancreatic Cancer - Hua, Qing; Li, Tianjiao; Liu, Yixuan; Shen, Xuefang; Zhu, Xiaoyan; Xu, Pingbo (Frontiers in Oncology, 2021)
Abstract Pancreatic ductal adenocarcinoma (PDAC) is a growing cause of cancer-related mortality worldwide. Kallikrein-related peptidase 8 (KLK8) has potential clinical values in many cancers. However, the clinicopathological significances of KLK8 in PDAC remain unknown. We explored the relationship of KLK8 to clinicopathological features of PDAC based on public databases. KLK8 expression was examined in human PDAC tissues. Cell proliferation and apoptosis were evaluated in KLK8-overexpressed human pancreatic cancer cell lines Mia-paca-2 and Panc-1. The related signaling pathways of KLK8 involved in pancreatic cancer progression were analyzed by gene set enrichment analysis (GSEA) and further verified in in vitro studies. We found that KLK8 was up-regulated in tumor tissues in the TCGA-PAAD cohort, and was an independent prognostic factor for both overall survival and disease-free survival of PDAC. KLK8 mRNA and protein expressions were increased in PDAC tissues compared with para-cancerous pancreas. KLK8 overexpression exerted pro-proliferation and anti-apoptotic functions in Mia-paca-2 and Panc-1 cells. GSEA analysis showed that KLK8 was positively associated with PI3K-Akt-mTOR and Notch pathways. KLK8-induced pro-proliferation and anti-apoptotic effects in Mia-paca-2 and Panc-1 cells were attenuated by inhibitors for PI3K, Akt, and mTOR, but not by inhibitor for Notch. In conclusion, KLK8 overexpression exerts pro-proliferation and anti-apoptotic functions in pancreatic cancer cells via PI3K/Akt/mTOR pathway. Upregulated KLK8 in PDAC predicts poor prognosis and may be a potential therapeutic target for PDAC.